2013
DOI: 10.1111/j.1365-4632.2012.05851.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of pachyonychia congenita with unusual manifestations: an unusual type or a new syndrome?

Abstract: A 30-year-old man presented with lesions on his oral mucosa and soles. There were no similar complaints in his family members. The dermatological examination revealed follicular hyperkeratosis on his trunk and upper extremities and flesh-colored, firm cystic lesions on his axillae. He had focal, painful, hyperkeratotic areas sited particularly on both his soles and palms. In addition to these, leukokeratosis and ulcerative areas on buccal, labial mucosa, tongue, and at corners of the mouth, and complete loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Eighteen studies evaluated national databases from Japan, 19 United States, 20,21 Denmark, 22 Taiwan, 23,24 and South Korea 25,26 . Fifty‐nine articles were case reports, 27–85 7 case series, 86–92 17 cross‐sectional, 19,21–26,93–102 and 2 case–control study 103,104 . One study 20 presented two different cohorts (retrospective and prospective case–control).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies evaluated national databases from Japan, 19 United States, 20,21 Denmark, 22 Taiwan, 23,24 and South Korea 25,26 . Fifty‐nine articles were case reports, 27–85 7 case series, 86–92 17 cross‐sectional, 19,21–26,93–102 and 2 case–control study 103,104 . One study 20 presented two different cohorts (retrospective and prospective case–control).…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory investigations were within normal limits except for a deficiency of immunoglobulin A. Keratin gene (KRT6a, KRT6b, KRT16, and KRT17) mutations for PC were negative. After the patient received a removable dental prosthesis, squamous cell cancer which is unexpected in oral lesions of PC developed on the lower lip mucosa during follow-up ( Figure 1 ) [ 8 ].…”
Section: Syndromesmentioning
confidence: 99%
“…In this patient, proximal layering of all the nails was unlike characteristic thickened dystrophic nails of PC. The authors suggested this case may be a new syndrome or an unusual new type of pachyonychia congenita because of this differing nail dystrophy, blepharitis, complete loss of teeth, and negative keratin gene mutations for pachyonychia congenita and developed squamous cell cancer on the oral leukokeratosis lesions [ 8 ].…”
Section: Syndromesmentioning
confidence: 99%
“…Akut febril nötro lik dermatoz olarak da bilinen hastalık ağrılı in amatuvar papül ve nodüllerden oluşmuş eritemli plaklar, ateş, nötro lik lökositoz ve dermiste yoğun nötro l in ltrasyonu ile karakterizedir 1,2 . Sweet sendromunun klinik ve histopatolojik olarak değerlendirildiği çalışmalar olmakla birlikte ülkemize ait Sweet sendromu ile ilgili yayınlar genellikle olgu bildirimi şeklindedir [3][4][5][6][7] . Ulusal çalışmalarda Öztaş ve ark.nın bildirdiği 8 olguya ait sadece bir çalışmaya rastladık 8 .…”
Section: Introductionunclassified